Gαi Signaling Promotes Marginal Zone B Cell Development by Enabling Transitional B Cell ADAM10 Expression - Hwang, Il-Young; Boularan, Cedric; Harrison, Kathleen; Kehrl, John H. (Frontiers in Immunology, 2018)
The follicular (FO) versus marginal zone (MZ) B cell fate decision in the spleen depends upon BCR, BAFF, and Notch2 signaling. Whether or how Gi signaling affects this fate decision is unknown. Here, we show that direct contact with Notch ligand expressing stromal cells (OP9-DL1) cannot promote normal MZ B cell development when progenitor B cells lack Gi proteins, or if Gi signaling is disabled. Consistent with faulty ADAM10 dependent Notch2 processing, Gi deficient transitional B cells had low ADAM10 membrane expression levels and reduced Notch2 target gene expression. Immunoblotting Gi deficient B cell lysates revealed a reduction in mature, processed ADAM10. Suggesting that Gi signaling promotes ADAM10 membrane expression, stimulating normal transitional B cells with CXCL12 raised it, while inhibiting Gi nucleotide exchange blocked its upregulation. Surprisingly, inhibiting Gi nucleotide exchange in transitional B cells also impaired the upregulation of ADAM10 that occurs following antigen receptor crosslinking. These results indicate that Gi signaling supports ADAM10 maturation and activity in transitional B cells, and ultimately Notch2 signaling to promote MZ B cell development.